Atomic Interaction Mechanism of Heterogeneous Nucleation in Mg-Al Alloys Achieved by Carbon Inoculation - Aimin Zhang; Ying Zhu; Kai Tao; Zhiyuan Zhang (Metals, 2025)
Theoretical calculations were performed to explore the heterogeneous nucleation mechanism of an Mg-Al alloy inoculated by a carbon-containing substance. The valence electron structure and cohesive energy of Al4C3 and Al2C2Mg crystals were calculated using the empirical electron theory of solids and molecules (EET). The binding energy of Al1-C2 bonds in Al4C3 is about 140.6 kJ/mol with a lower number of equivalent bonds. Correspondingly, the binding energy of Al2-C2 bonds is about 129.6 kJ/mol, and the number of equivalent bonds is high. The weak combination of the Al1 and C2 atomic layers might lead to the breaking of Al4C3, and then the remaining strong skeleton of the Al2-C2 structure will facilitate the formation of Al2C2Mg. Based on the calculating results, the atomic interaction mechanism to account for the heterogeneous nucleation of α-Mg by C inoculation is elaborated, which also provides insights into the essence of the overheating process and the influence of Al and Mn elements on the refinement efficiency of Al2C2Mg.